Polyclonal antibody production against rGPC3 and their application in diagnosis of hepatocellular carcinoma. Issue 5 (28th May 2018) - Wang, Shenghao; Kalim, Muhammad; Liang, Keying; Zhan, Jinbiao
ABSTRACT: Glypican-3 (GPC3) is an integral membrane proteoglycan, which contains a core protein anchored to the cytoplasmic membrane through a glycosylphosphatidylinositol linkage. The glypican-3 can regulate the signaling pathways, thereby enhances cell division, growth, and apoptosis in certain cell types. It is almost nonexistent on the surface of the human normal cell membrane and highly expresses on the membrane of hepatocellular carcinoma (HCC) cells. It has been well established that GPC3 provides a useful diagnostic marker. For generating the polyclonal antibody of GPC3, we expected that GPC3 N-terminal region (amino acid sequence 26–358) could be expressed in Escherichia coli system, however, no active expression was observed after IPTG induction. Interestingly, after deletion of six proline residues from position 26 to 31 in the N-terminus, expression of recombinant GPC3 was clearly detected. We further analyzed the expressed protein deprived of six prolines, to immunize the New Zealand male rabbits for production of active antibodies. The binding affinity of antibody was analyzed by immunofluorescence analysis, immunohistochemical detection, and western blotting. The functional GPC3 N-terminal protein recombinant development, expression, purification, and the polyclonal antibody have been generated provide the basis for the diagnosis of HCC in cancer therapy.